Successful percentage of action in mandibular block injection training using Fischer’s technique - Uthophia, Natrisa; Gunawan, Kirana Lina; Yuza, Abel Tasman (Padjadjaran Journal of Dentistry, 2015)
Introduction: Injecting a local anaesthetic amongst students is part of the dentistry education in many countries. Mandibular block injection technique used in the Faculty of Dentistry Universitas Padjadjaran is Fischer’s technique. The purpose of this study was to determine the success rate based on the average onset and duration of action in mandibular block injection training using Fischer’s technique conducted by the 8th-semester students of the Faculty of Dentistry Universitas Padjadjaran batch 2008. Methods: The method of this study was a descriptive survey—sampling method used was the purposive sampling technique. Data was obtained through the questionnaires distributed to 100 students who practice injection using Fischer’s technique. Anaesthetics used on these injection training was 2% lidocaine HCl with epinephrine 1:80,000. Results: The success rate of mandibular block injection using Fischer’s technique was 88% (88 from 100 injections), with an average onset of action was 2.33 minutes and the average duration of action was 194.07 minutes. Conclusion: The percentage of success in injection training with Fischer’s technique was high, with appropriate average onset and duration of action by the existing standards.